Role of the Receptor for Advanced Glycation End Products in Heat Stress-Induced Endothelial Hyperpermeability in Acute Lung Injury - Zhou, Gengbiao; Chen, Zhenfeng; Li, Jieyu; Guo, Xiaotong; Qin, Kaiwen; Luo, Jiaqi; Hu, Jiaqing; Huang, Qiaobing; Su, Lei; Guo, Xiaohua; Xu, Qiulin (Frontiers in Physiology, 2020)
Objective: To study the role of RAGE (receptor for advanced glycation end products) in the endothelial barrier dysfunction induced by heat stress and further explore the signal pathway by which RAGE contributes to heat-induced endothelia response, and thereby find a novel target for the clinical treatment of ALI (acute lung injury) induced by heatstroke. Methods: Established the animal model of heatstroke by using RAGE knockout mice, and observed the role of RAGE in acute lung injury induced by heatstroke in mice by evaluating the leukocytes, neutrophils and protein concentration in BALF (Bronchoalveolar lavage fluids), lung wet/dry ratio, histopathological changes and morphological ultrastructure of lung tissue and arterial blood gas analysis. To further study the mechanism, we established heat stress model of HUVEC and spotlighted the role of RAGE and its signal pathway in the endothelial barrier dysfunction induced by heat stress by measuring Transendothelial electrical resistance (TEER) and western blot. Results: RAGE played a key role in acute lung injury induced by heatstroke in mice. In mechanism, C-Jun located to the promoter region of RAGE gene and increased the RAGE protein expression while HSF1 suppressed RAGE protein expression. The overexpressed RAGE protein expression then further increased HUVEC monolayer permeability by activating ERK and P38 MAPK under heat stress. Conclusion: In summary, this study indicates the critical role of RAGE in heat stress-induced endothelial hyperpermeability in acute lung injury and suggests that RAGE maybe serves as a potential therapeutic target in protecting against acute lung injury induced by heatstroke.